Girls and Violence : Tracing the Roots of Criminal Behavior. - Ryder, Judith A. (Lynne Rienner Publishers, 2012)
Seeking to better understand the processes that push teenage girls to acts of criminal violence, Judith Ryder explores the relationship between disrupted emotional bonds and violent delinquency. Ryder draws on intimate interviews to show how teenage girls navigate experiences of abuse, emotional loss, and parental abandonment, revealing how their violent acts become a means of connecting with others-however maladaptive and misplaced those connections may be. Her work suggests viable strategies for early intervention to keep at-risk young women out of the criminal justice system.